The vertical metallicity gradients of mono-age stellar populations in the Milky Way with the RAVE and Gaia data. Issue 1 (21st December 2017) - Ciucă, Ioana; Kawata, Daisuke; Lin, Jane; Casagrande, Luca; Seabroke, George; Cropper, Mark
Abstract: We investigate the vertical metallicity gradients of five mono-age stellar populations between 0 and 11 Gyr for a sample of 18 435 dwarf stars selected from the cross-matched Tycho- Gaia Astrometric Solution and Radial Velocity Experiment (RAVE) Data Release 5. We find a correlation between the vertical metallicity gradients and age, with no vertical metallicity gradient in the youngest population and an increasingly steeper negative vertical metallicity gradient for the older stellar populations. The metallicity at disc plane remains almost constant between 2 and 8 Gyr, and it becomes significantly lower for the 8 < τ ≤ 11 Gyr population. The current analysis also reveals that the intrinsic dispersion in metallicity increases steadily with age. We discuss that our results are consistent with a scenario that (thin) disc stars formed from a flaring (thin) star-forming disc.